(untitled) - Hames, B. D. (New York, N.Y., 2005)
Instant Notes titles focus on core information and are designed to help undergraduate students come to grips with a subject quickly and easily. A major update of the highly popular second edition, with changes in the content and organization that reflect advances in the subject. New and expanded topics include cytoskeleton, molecular motors, bioimaging, biomembranes, cell signaling, protein structure, and enzyme regulation. As with the first two editions, the third edition of Instant Notes in Biochemistry provides the essential facts of biochemistry with detailed explanations and clear illustrations.
Keywords: Biochemistry,Hóa sinh học